Crazy bones: evidence of insanity in the skeletal collection of the Colorado State Insane Asylum - McGloin, Cashel A., author; Magennis, Ann, advisor; Ore, Janet, committee member; Van Buren, Mary, committee member (Colorado State University. Libraries, 2012)
Excavations of a forgotten cemetery of the Colorado Insane Asylum yielded the skeletons of approximately 155 individuals buried between 1879 and 1899. The collection exhibited a number of abnormalities that could be related to pathological conditions that may have been the cause of insanity for those present. The skeletons were examined for abnormalities, especially to the crania, and these abnormalities were compared to conditions that may have afflicted Victorian populations and resulted in insanity. In particular, several crania, while normal in appearance, were extremely heavy. Radiographs were taken of these crania to see if any pathological conditions known to be associated with both heavy crania and insanity could be found. Forty of the skeletons were tested for the presence of heavy metals, specifically focusing on the individuals who had signs of syphilis. It was hoped that, as mercury was the most common treatment for syphilis at the time, the presence of mercury might be useful in distinguishing syphilitic infection from other pathologies of the bone. Arsenic, copper, lead, manganese and zinc levels were also examined, as all were metals common in the period of the asylum, and all are associated with mental disruptions in high enough doses. Although it is not possible to definitely link skeletal remains to specific mental conditions, some abnormalities that seem to be linked to insanity were found.
Keywords: asylum; bioarchaeology; Colorado; insanity; skeletal; Victorian